Mesothelin-specific Immune Responses Predict Survival of Patients With Brain Metastasis - Zhenjiang, Liu (EBioMedicine, 2017)
BACKGROUND: Patients with advanced malignancies, e.g. lung cancer, ovarian cancer or melanoma, frequently present with brain metastases. Clinical presentation and disease progression of cancer is in part shaped by the interaction of the immune system with malignant cells. Antigen-targeted immune responses have been implicated in the prolonged survival of patients with cancer. This includes the tumor-associated antigen (TAA) mature mesothelin, a 40 kDa cell surface-bound antigen that is overexpressed in several malignancies including lung ovarian and pancreatic cancer. We examined in an observational, prospective study the survival of patients with brain metastases in association with clinical parameters and cellular immune responses to molecularly defined TAAs or viral (control) target antigens. METHODS: Immune cells in peripheral blood obtained from thirty-six patients with brain metastases were tested for cytokine production in response to a broad panel of defined viral and TAA target antigens, including full-length mesothelin. Incubation of immune cells with antigenic targets was carried out in i) medium alone, (ii) in a cytokine cocktail of interleukin (IL)-2/IL-15/IL-21, or (iii) IL-2/IL-7. Supernatants were tested for interferon gamma (IFN-γ) production, after which univariate and multivariate analyses (Cox stepwise regression model) were performed to identify independent clinical and immunological factors associated with patient survival. Patients were followed-up for at least 500 days after surgery or until death. FINDINGS: Univariate analysis identified age, gender, radiotherapy and mutational load as clinical parameters affecting survival of patients with brain metastases. Cox multivariate analysis showed that radiotherapy (P = 0·004), age (P = 0·029) and IFN-γ responses to mature mesothelin, conditioned by IL-2/IL-7 (P = 0·045) were independent predictors of the survival of patients from surgery up to follow-up or death. INTERPRETATION: This is the first evidence that immune responses to mesothelin serve as a marker of increased overall survival in patients with brain metastases, regardless of the primary tumor origin. Analyses of immunological markers could potentially serve as prognostic markers in patients with brain metastases and help to select patients in need for adjunct, immunological, treatment strategies.